Knowledge of self-management and asthma control among asthma patients attending a polyclinic in Western part of Singapore - Joanne H. Khor; Anna Szücs; Lay Hoon Goh (Journal of Family and Community Medicine)
BACKGROUND: Self-management is important for asthma control, yet it is unclear whether asthmatic patients have sufficient knowledge to optimally manage their disease. We examined the associations between the knowledge of self-management in adult patients attending a polyclinic in Singapore, sociodemographic factors, and asthma control. MATERIALS AND METHODS: A cross-sectional survey was conducted among adult asthmatic patients in a public primary care clinic (polyclinic) using convenience sampling. A a structured and validated self-administered questionnaire solicited the responses of study participants. Questionnaire comprised three sections: (1) Sociodemographic and asthma-related variables, (2) Modified Asthma Self-Management Questionnaire (ASMQ), and (3) The GINA assessment of asthma control. Participants completed the questionnaire in the clinic waiting area and returned them into a sealed box in the same area. Data were analyzed using SPSS version 29.0. Summary statistics were used to describe the study sample; t-test or analysis of variance (ANOVA), as appropriate, tested the differences in self-management knowledge by sociodemographic characteristics. Logistic regression was used to determine the association between asthma control and self-management knowledge controlling for sociodemographic characteristics. RESULTS: The sample comprised 141 asthma patients; Out of a total of 100 points, the mean ASMQ score was 46.8 (standard deviation 21.7). The scores for the knowledge of self-management of Asthma differed by age, level of education, and having been taught about asthma on bivariate analyses (P < 0.05). Linear regression showed a significant association of asthma self-management knowledge with educational level only. No association was observed between ASMQ scores and asthma control. CONCLUSION: There were gaps in patients’ knowledge about asthma self-management, although they were generally knowledgeable about the inhaler technique. Higher education levels were associated with higher levels of knowledge beyond the effect of age and having been instructed about asthma, suggest that it is crucial that educational programs on asthma are made accessible to patients with lower levels of education. Further research needs to determine whether asthma educational programs targeting the knowledge gaps found in this study can improve knowledge of self-management and asthma control.